Mandibular advancement reduces pharyngeal collapsibility by enlarging the airway rather than affecting velopharyngeal compliance - Guilherme J. M. Garcia; Josiah J. Wolf; David A. Campbell; Ryan S. Bailey; Rodney A. Sparapani; Charles M. Welzig; B. Tucker Woodson (Physiological Reports, 2023)
Abstract Mandibular advancement devices (MADs) are frequently prescribed for obstructive sleep apnea (OSA) patients, but approximately one third of patients experience no therapeutic benefit. Understanding the mechanisms by which MADs prevent pharyngeal collapse may help optimize MAD therapy. This study quantified the relative contributions of changes in airspace cross‐sectional area (CSA) versus changes in velopharyngeal compliance in determining MAD efficacy. Sixteen patients with moderate to severe OSA (mean apnea–hypopnea index of 32 ± 15 events/h) underwent measurements of the velopharyngeal closing pressure (PCLOSE) during drug induced sedated endoscopy (DISE) via stepwise reductions in nasal mask pressure and recording of the intraluminal pressure with a catheter. Airspace CSA was estimated from video endoscopy. Pharyngeal compliance was defined as the slope of the area–pressure relationship of the velopharyngeal airspace. MAD therapy reduced PCLOSE from a median of 0.5 cmH2O pre‐advancement to a median of −2.6 cmH2O post‐advancement (p = 0.0009), increased the minimal CSA at the velopharynx by approximately 20 mm2 (p = 0.0067), but did not have a statistically significant effect on velopharyngeal compliance (p = 0.23). PCLOSE had a strong correlation with CSA but did not correlate with velopharyngeal compliance. Our results suggest that MADs reduce velopharyngeal collapsibility by increasing airway size as opposed to affecting velopharyngeal compliance. This contradicts the speculation of previous literature that the effectiveness of MADs is partially due to a reduction in velopharyngeal compliance resulting from stretching of the soft palate. These findings suggest that quantification of velopharyngeal CSA pre‐ and post‐MAD advancement has potential as a biomarker to predict the success of MAD therapy.